Delegates at the Second Congress and General Assembly of the International Union of Crystallography (1951)
Black and white photograph of delegates at the Second Congress and General Assembly of the International Union of Crystallography (IUCr), Stockholm, Sweden, 27 June - 3 July 1951. The photograph was taken outside the University Building in Uppsala.
Keywords: International Union of Crystallography; Congresses and conventions; Uppsala universitet